Thermomechanical tool load in the machining of spheroidal cast iron – aluminium compounds. (27th June 2011) - Denkena, B.; de León, L.; Lucas, A.; Meyer, R.
There is an increasing use of parallel compounds in the industry in which the compound has to be machined within one cut. The machinability of these compounds differs from that of the homogenous separate materials. In this paper, machining tests with compounds out of hard and soft materials (spheroidal cast iron and aluminium) are presented. The mechanical and thermal load on the tool cutting edge and its wear behaviour are examined regarding their dependency on the cutting parameters and the material ratio. The results show that the tool life decreases considerably with an increasing proportion of hard material in a compound. Furthermore, the tool wear limit is reached faster when the cut is performed in the direction from the hard into the soft material. The cutting direction also influences the process forces. In order to minimise the load occurring on the tool, the cut should be performed in the direction from the soft into the hard material.